N- Myristoyltransferase as a potential drug target in malaria and leishmaniasis - Tate,EW; Bell,AS; Rackham,MD; Wright,AH (Parasitology, 2013)
Infections caused by protozoan parasites are among the most widespread and intractable transmissible diseases affecting the developing world, with malaria and leishmaniasis being the most costly in terms of morbidity and mortality. Although new drugs are urgently required against both diseases in the face of ever-rising resistance to frontline therapies, very few candidates passing through development pipelines possess a known and novel mode of action. Set in the context of drugs currently in use and under development, we present the evidence for N-myristoyltransferase (NMT), an enzyme that N-terminally lipidates a wide range of specific target proteins through post-translational modification, as a potential drug target in malaria and the leishmaniases. We discuss the limitations of current knowledge regarding the downstream targets of this enzyme in protozoa, and our recent progress towards potent cell-active NMT inhibitors against the most clinically-relevant species of parasite. Finally, we outline the next steps required in terms of both tools to understand N-myristoylation in protozoan parasites, and the generation of potential development candidates based on the output of our recently-reported high-throughput screens.